A quasi-experimental study provides evidence that registered dietitian nutritionist care is aligned with the Academy of Nutrition and Dietetics evidence-based nutrition practice guidelines for type 1 and 2 diabetes - Lamers-Johnson, Erin; Kelley, Kathryn; Knippen, Kerri Lynn; Feddersen, Kimberly; Sánchez, Damien M.; Parrott, J. Scott; Colin, Casey; Papoutsakis, Constantina; Jimenez, Elizabeth Yakes (Frontiers in Nutrition, 2022)
Background One previous study examined implementation of evidence-based nutrition practice guidelines (EBNPG). Objectives To describe alignment of registered dietitian nutritionists' (RDNs) documented nutrition care with the Academy of Nutrition and Dietetics' EBNPG for Type 1 and Type 2 diabetes and examine impact of a midpoint training on care alignment with the guideline. Methods In this 2-year, quasi-experimental study, 19 RDNs providing outpatient medical nutrition therapy to adults with diabetes (n = 562) documented 787 initial and follow-up encounters. At study midpoint, RDNs received a guideline content training. A validated, automated tool was used to match standardized nutrition care process terminology (NCPT) in the documentation to NCPT expected to represent guideline implementation. A congruence score ranging from 0 (recommendation not identified) to 4 (recommendation fully implemented) was generated based on matching. Multilevel linear regression was used to examine pre-to-post training changes in congruence scores. Results Most patients ( 75%) had only one documented RDN encounter. At least one guideline recommendation was fully implemented in 67% of encounters. The recommendations “individualize macronutrient composition” and “education on glucose monitoring” (partially or fully implemented in 85 and 79% of encounters, respectively) were most frequently implemented. The mean encounter congruence scores were not different from pre-to-post guideline training (n = 19 RDNs, 519 encounters pre-training; n = 14 RDNs, 204 encounters post-training; β = −0.06, SE = 0.04; 95% CI: −0.14, 0.03). Conclusions Most RDN encounters had documented evidence that at least one recommendation from the EBNPG was implemented. The most frequently implemented recommendations were related to improving glycemic control. A midpoint guideline training had no impact on alignment of care with the guideline.